Analisis Dampak Perilaku Bullying terhadap Prestasi Belajar Peserta Didik pada Tingkat Madrasah Ibitidaiyah dan Sekolah Dasar - Hardianto Rahman; Muhammad Irfan; Diarti Andra Ningsih; Hasmiati Hasmiati; Saydiman Saydiman; Hasfira Asri (Journal on Education, 2023)
This study aims to: 1) determine the effect of bullying behaviour on student achievement; 2) Analyze the impact of bullying behaviour and its impact on learning achievement. This research includes ex post facto research conducted based on events or phenomena to find bullying behaviour on learning achievement and other impacts on students. The approach taken is a descriptive quantitative approach and a literature review method. This method is used to collect, identify, evaluate and interpret articles describing the impact of bullying behaviour in madrasah and elementary schools. The results showed that bullying behaviour impacted students' learning achievement. Shows that 15.4% of student achievement at MIN 2 Sinjai is influenced by bullying behaviour, and other causes affect the remaining 84.6%. Through the literature review method, it was found that bullying behaviour can impact poor socialization, low self-confidence, decreased self-esteem in the future, low social skills of students, inability to communicate with others, experience depression, anxiety, and the possibility of self-harm.